Optimization of Ship Crew Placement in Accordance with Safe Manning at PT. Pertamina International Shipping (PIS) - Prasetiawan, Andi; Sengadji, Carolus Geleuk; Gedalya, Kevin Zefano (RSF Conference Series: Engineering and Technology, 2023)
Placement of ship crew that is not in accordance with safe manning at PT. Pertamina International Shipping (PIS) is due to the limitations and availability of crew being the main cause of the uneven placement of crew, the lack of crew members who have essential skills or certifications for a particular division, so an even distribution of ships cannot be achieved. Sending ship crew to carry out tasks on board must be in accordance with existing provisions and procedures. Crew competency certificates (COC) and skills (COP) must have met the validity according to the 2010 STCW amendments. The purpose of this study was to describe the factors that cause the uneven placement of ship crew in each division of the manning fleet. And to find out the efforts made by PT. Pertamina International Shipping in overcoming the uneven placement and delivery of ship crew in each manning fleet. The research method used is the descriptive qualitative method. Sources of research data obtained from primary data and secondary data. Data collection techniques through observation, documentation, and interviews. As well as a SWOT analysis. The research results show that the internal and external factors that influence the placement and distribution of crew in each division of the manning fleet are condition, work experience, demand from the company and supply of prospective crew to be selected, incomplete certificates, and interest from prospective crew members. As well as the efforts made by PT. Pertamina International Shipping in handling the problem of placing and sending ship crew for each manning fleet, is the placement and sending of ship crew according to the needs of the ship, referring to shipping regulations as well as provisions and structural positions in the company.